Characteristics and controlling factors of seismic site response at a crystalline bedrock site based on quality factor inversion using deep borehole data - Naoki Nishizaka; Hiroaki Sato; Takeshi Tsuji; Yoshihiko Ishikawa; Chiaki Nagai; Yasutomo Yamauchi (Scientific Reports)
Abstract This study evaluated epistemic uncertainty in shear-wave velocity (Vs) profiles and variability in shear-wave quality factor (Qs) profiles across broadband frequencies to investigate characteristics and controlling factors of seismic site response at a crystalline bedrock site. This study utilized deep borehole data down to the seismological bedrock at a depth of 2000 m. Multiple invasive measurements were conducted to estimate the Vs profiles. Three-component seismometers were installed at depths of 5, 160, 500, and 2000 m for Qs profiling. A logic tree with 128 analysis patterns was employed to capture the frequency-dependent percentiles of the amplification factor (AF) and the Qs parameter through spectral ratio Qs inversions. AFs from depths of 2000 m to 5 m showed the attenuation effect was dominant in the frequency range above 1 Hz. Sensitivity analysis revealed the dominant effects of the Qs profile below 2 Hz and above 15 Hz and the significant effects of the Vs profile at 2–15 Hz. The median AF curves were robust due to multiple invasive measurements and constraints from reliable seismic records. Local site responses captured from the 2000- m borehole station are expected to contribute to seismic hazard assessments as a reference of crystalline bedrock sites.